Endometriosis and Infertility: How and When to Treat? - Fadhlaoui, Anis (Front Surg, 2014)
Endometriosis is defined as the presence of endometrial-like tissue (glands or stroma) outside the uterus, which induces a chronic inflammatory reaction. Although endometriosis impairs fertility, it does not usually completely prevent conception. The question of evidence based-medicine guidelines in endometriosis-associated infertility is weak in many situations. Therefore, we will highlight in this issue where the challenges are.